2022
DOI: 10.3390/vetsci9080418
|View full text |Cite
|
Sign up to set email alerts
|

Use of Maca Powder (Lepidium meyenii) as Feed Additive in Diets of Laying Quails at Different Ages: Its Effect on Performance, Eggshell Quality, Serum, Ileum, and Bone Properties

Abstract: Using additives can reduce the negative effects of aging on factors affecting profitability, such as the availability of nutrients, production, and egg quality. Maca is an herbaceous plant rich in protein, crude oil, essential acids, and pharmacological compounds. Maca has positive effects on different health parameters. In this study, the effect of adding Maca powder to the diets of young and old laying quails at the end of the 10-week trial was investigated. In total, 150 laying Japanese quails (Coturnix jap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…Egg weight was determined by weighing one by one all of the eggs collected in the last three days of the experiment with a precision weighing balance (±0.01 g). From these data, egg mass was calculated as daily egg weight per quail according to the following Equation (1), as Gül et al [ 21 ] showed in their research. …”
Section: Methodsmentioning
confidence: 99%
“…Egg weight was determined by weighing one by one all of the eggs collected in the last three days of the experiment with a precision weighing balance (±0.01 g). From these data, egg mass was calculated as daily egg weight per quail according to the following Equation (1), as Gül et al [ 21 ] showed in their research. …”
Section: Methodsmentioning
confidence: 99%
“…Additionally, muscle strength ( p < 0.01), muscle endurance ( p < 0.01), flexibility ( p < 0.01), power ( p < 0.001), and agility ( p < 0.001) were significantly increased in the FSA group after taking black maca supplementation for eight weeks. Earlier, the addition of arginine was mentioned as a component of black maca [ 31 ]. Arginine is an amino acid that has shown a vasodilator effect [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…From these data, egg mass was calculated as daily egg weight per quail (g) according to the equation proposed by Gül et al . (2022) (Eqn (1))…”
Section: Methodsmentioning
confidence: 99%
“…Eggshell quality has been a major economic concern to egg producers as it could reason for serious economic losses (Joshi et al ., 2019; Gül et al ., 2022). Eggshell has different functions such as protects against physical damage and pathogens coming from the external environment, and providing nutrients necessary for embryonic development, especially calcium.…”
Section: Introductionmentioning
confidence: 99%